Analisis Rasio Kinerja Keuangan pada PT Kimia Farma Tbk Periode Tahun 2018 – 2022 - Aldila Kurnia Dian Permata Sari (Universitas Veteran Bangun Nusantara, 2024)
The aim of this research is to analyze the financial condition and performance of PT. Kimia Farma Tbk during the 2018-2022 period. The type of research used was quantitative descriptive. using financial report analysis methods and financial ratios. The horizontal analysis method is used to see the company's development over time. Evaluation is carried out mainly on liquidity ratios (Current Ratio and Quick Ratio), solvency ratio analysis (Debt to Asset Ratio and Debt to Equity Ratio), profitability ratio analysis (Net Profit Margin and Return On Investment), and activity ratio analysis (Total Assets Turn Over and Inventory Turn Over). The results show fluctuations in the company's liquidity, indicating significant challenges in current debt management. Solvency ratios show high levels of debt, emphasizing the need for funding diversification. Profitability ratios describe obstacles in generating net profits and competitiveness in the market. The activity ratio shows performance that has not reached standards in inventory management and asset utilization. These findings provide insight into the company's financial condition and highlight aspects that need improvement, in the hope of contributing to the development of more effective financial strategies.